Kendala-Kendala dalam Penerapan Flexible Working Arrangement di Perusahaan Pengembangan Perangkat Lunak dan Penanggulangan - Benny Susanto; Wisnujaya Nugraha; Andris Gunawan; Mega; Wilson Bangun (Jurnal Informatika Ekonomi Bisnis, 2023)
The implementation of flexible working in various software development companies has been widely adopted, but behind the popularity of the system, there are various visible and hidden issues. Most companies still feel unprepared to implement the system due to a lack of standardization regarding the procedures for implementing the said system. This article aims to identify the various problems and challenges that arise in the implementation of the system and the best practices to address them. Data was collected from three software development companies in Bandung using observation and interviews as the research methods. Questionnaires were also used to gather data on the extent of adoption of these mitigation practices.